Upaya Meningkatkan Hasil Belajar Informatika Menggunakan Model Roleplay Topik Percabangan - JB Suhatmaji Sunaryo (Media Manajemen Pendidikan, 2023)
The purpose of this study was to determine the implementation of the Role Play learning method in an effort to increase student motivation in the subject matter. Conditional instruction syntax: if the, if then else, case, syntax for various loops available in the programming language used for the execution mechanism for each type of instruction.This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle that is carried out consists of four stages, namely the planning stage, the implementation stage, the observation stage and the reflection stage. As for the subjects of the research, there were 36 students in class X MIPA 3 of SMA Negeri 1 Sedayu. Data collection techniques using observation techniques, tests, documentation regarding the implementation of the Role Play learning method. The data analysis technique used is quantitative analysisBased on the results of the study it was concluded that the implementation of the Role Play learning method could increase the learning motivation of class X MIPA 3 SMA Negeri 1 Sedayu as evidenced by an increase in the percentage of student learning outcomes in the LESS category from cycle I, increasing to 66% in cycle II. If viewed classically, student motivation in the Enough category also increased to 11%, while the Good Category increased 39%, and the VERY GOOD category increased 38% in cycle II..